2017
DOI: 10.1186/s12883-017-0957-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expressions of hereditary Transthyretin Ala97Ser related Amyloidosis (ATTR) in Taiwanese

Abstract: BackgroundThe disease course and early signs specific to ATTR Ala97Ser, the most common endemic mutation in Taiwan, have not been well described. Since new medications can slow down the rate of disease progression, the early diagnosis of this heterogeneous and fatal disease becomes critical.MethodsWe retrospectively reviewed the characteristics of genetically confirmed ATTR Ala97Ser patients at a tertiary referral medical center.ResultsEight patients from 7 different families were enrolled (61.7 ± 5.5 years). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
5
23
0
Order By: Relevance
“…Gastrointestinal dysfunctions and orthostatic intolerance were the most prevalent autonomic complaints. Gastrointestinal symptoms seemed to present in the early phase of disease, like previous studies [ 7 , 10 , 20 ]. Sudomotor dysfunction, though frequently evident by neurophysiological tests (the results of 7/7 QSART tested patients were abnormal.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Gastrointestinal dysfunctions and orthostatic intolerance were the most prevalent autonomic complaints. Gastrointestinal symptoms seemed to present in the early phase of disease, like previous studies [ 7 , 10 , 20 ]. Sudomotor dysfunction, though frequently evident by neurophysiological tests (the results of 7/7 QSART tested patients were abnormal.…”
Section: Discussionsupporting
confidence: 82%
“…Motor neuropathy appeared in the later stage of disease and was usually accompanied by significant weight reduction. Weight reduction has been hypothesized to be due to gastrointestinal dysautonomia, dysphagia and muscular atrophy [ 7 ]. Of interest, our study showed that when motor neuropathy was present, the overall worsening of neuropathy tended to progress faster than when motor neuropathy was not present in both clinical and neurophysiological aspects (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OH is also prevalent and severe in patients with some non-Val30Met mutations [12, 15, 20, 24, 25, 27, 49, 53, 57, 60, 69, 73, 78, 79, 95, 96, 113, 115, 119, 136, 137, 142, 145]. For instance, up to 100% of patients with the Ala97Ser mutation have OH, with 71% having frequent syncope, particularly in late stages of the disease [58].…”
Section: Epidemiology Of Oh In Hereditary Ttr Amyloidosismentioning
confidence: 99%